2020
DOI: 10.33846/hn40701
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Strawberry Extract with 100% Concentration in Cleaning Teeth with Extrinsic Stain at the Academic Community of Poltekkes Kemenkes Jakarta I

Abstract: Discoloration of teeth can be caused by stains on the surface of the teeth or due to changes in tooth material. Tooth stain can be extrinsic, intrinsic, or age-related. Tooth whitening (bleaching) can be done in the office and at home. Strawberry is a fruit with many benefits, one of which is whitening teeth. The content of malic acid and ellagic acid in strawberries has the effect of tooth whitening. The purpose of this study was to determine the effectiveness of strawberry extract with a concentration of 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…This research is in line with previous research conducted by Karmawati et al (2015), where the application of crushed strawberries carried out for 5 consecutive days can significantly reduce the staining score [18]. Karmawati (2020), said that the effect of a strawberry extract with a concentration of 100% on the disappearance of extrinsic stains did not even take up to 5 days of treatment for some respondents, because the respondent's staining score had reached 0 before the 5th day. It can be stated that strawberry fruit extract with a concentration of 100% can remove extrinsic stains on teeth effectively within 2 to 4 days.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This research is in line with previous research conducted by Karmawati et al (2015), where the application of crushed strawberries carried out for 5 consecutive days can significantly reduce the staining score [18]. Karmawati (2020), said that the effect of a strawberry extract with a concentration of 100% on the disappearance of extrinsic stains did not even take up to 5 days of treatment for some respondents, because the respondent's staining score had reached 0 before the 5th day. It can be stated that strawberry fruit extract with a concentration of 100% can remove extrinsic stains on teeth effectively within 2 to 4 days.…”
Section: Discussionsupporting
confidence: 91%
“…The biggest decrease in the average Combined Score occurred on the 2nd day, from a score of 20.0 on the 1st day to 14.6 on the 2nd day with a percentage decrease of 35.0%. The statistical test showed a significant result of 0.000 reducing the intensity score and area score from the 2nd day to the 5th day [7]. Radhakrishnan (2021) stated that whitening tooth enamel with strawberry fruit extract with a concentration of 2% can efficiently and effectively whiten the surface without significant adverse effects on the enamel surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, research concluded that the use of Carbamid Peroxide 2 percent 60 seconds a day for 3 days alone can significantly cause inflammation of the oral mucosa. [3][4][5] Corresponding Author: Ita Astit Karmawati…”
Section: Introductionmentioning
confidence: 99%